PEG-based hydrogel-coated test strip for on-site urea determination - YARAT, AYŞEN; KAHRAMAN, MEMET VEZİR (TAYLOR & FRANCIS AS, 2019)
The urea test strip was prepared using polyethyleneglycol based hydrogel, urease and commercial pH-indicator paper. The swelling behavior of hydrogel indicated the ability of the urea to penetrate into the matrix and allowing the test strip to respond in a short time. The color formed on the strip was distinguished by naked eyes in one minute at room temperature. The linear range for urea was 20-200 mg/dL. The assays have good reproducibility. Relative standard deviation values were found within the range of 3.37-12.95% and 1.68-9.54% for intra- and inter-day assays, respectively.
Keywords: Colorimetric biosensor; PEG-based hydrogel; urea test strip; urease; IMMOBILIZATION; BIOSENSOR; BLOOD; MICROPARTICLES; ELECTRODE; NITROGEN; ARRAYS